Nilai-nilai Karakter Damai “To Ugi” dalam Sureq I La Galigo Epsiode Mula Rioluna Batara Guru - Hikmah, Muh. Syawal; Fathan, A. As'ad; Yusri, Akbar Gibran (YASIN, 2025)
This study explores the values ​​of peaceful character in the sureq I La Galigo episode Mula Rioluna Batara Guru which aims to identify and analyze the values ​​of To Ugi's peaceful character contained in the sureq I La Galigo. This study uses a qualitative descriptive method with a Wilhelm Dilthey hermeneutic approach, by interpreting the script (sureq) based on experience, expression, and understanding of Bugis culture. The results of the reserch show that the values ​​of To Ugi's peaceful character in the sureq La Galigo episode Mula Rioluna Batara Guru include, a good heart, caution and alertness to avoid danger, the appropriateness of speech and actions 'adanagau' or conformity and action, not arrogant or humble, thinking before acting, togetherness (mutual cooperation), honesty and true words (lempu sibawa ada tongeng), loyalty (solidarity), friendship, and responsibility and affection which are integral parts in building a harmonious and peaceful social life. In the midst of the development of the era that brings moral challenges to the younger generation, understanding local cultural values ​​is important as a foundation for peaceful character education. Therefore, this study emphasizes the importance of integrating peaceful character values ​​in learning and social life to form individuals who are moral and have peaceful characters.